Contaminação por metais pesados em cisne-do-pescoço-preto (Cygnus melanocoryphus) no Sul do Brasil - Rosa, Nathaly Nunes da (Universidade Federal Rural do Semi-Árido, 2017)
The black-necked swan (Cygnus melanocoryphus) is endemic to South America, and in the extreme south Brazil is found in Lagoa Mangueira, which is part of the Taim Ecological Station (ESEC Taim). This region is characterized by the practice of rhiziculture and its effluents generated with contaminants, are released inside the lagoon, and can affect the life of C. melanocoryphus. Despite this, there are not many papers evaluating the environmental contamination by heavy metals in this place and there are no works in relation to the contamination with this species of swan. The objective of this study, was to evaluate the concentrations of copper (Cu), cadmium (Cd), chromium (Cr), nickel (Ni), lead (Pb) and Zn (Zn) present in the two excretion pathways (faeces and feathers) and a blood circulation pathway of C. melanocoryphus, comparing seasonally, between the sexes and ages and to see if there is relation between the size of the ninth feather of the wing of this species with the concentrations of these metals. A total of 88 individuals were captured, where 61 individuals were sampled in the summer, 12 in the autumn and 15 in the winter. Samples of feathers, blood and feces were collected and taken to acid digestion for further analysis of the Cd, Cr, Cu, Pb and Zn metals by atomic absorption spectrometry. Simple regressions were made to evaluate the relationship between the concentrations of metals found in the origins (faeces, blood and feathers) with the length of the ninth primary wing of the wing of C. melancoryphus (indicating how long the individual is in place). Covariance analyzes (covariance: 9th primary ridge) were performed to assess whether the concentrations of metals at the origins differ according to the age and sex of the individuals. Finally, Factorial Anovas were performed to compare the concentrations of metals in feathers, blood and feces, differing throughout the seasons. Positive relationships were observed between Cu and Pb concentrations in faeces, Cu and Zn in feathers and Zn in blood (p <0.05), for the others no relation was found. Only the concentration of Zn for sex and age presented a significant difference. And for the seasons, only Zn and Cu showed significant positive differences. In this way, the concentrations of Cd and Pb found in feces were superior to other studies using swan species, so that C. melanocoryphus may be suffering from local contamination. For the other metals Cu and Zn, in feces feathers and blood, are inferior or equal to other works, and as they are essential metals they do not present toxicity to the organism
Contamination by heavy metals in black-neck swan (Cygnus melanocoryphus) in South of Brazil
Keywords: Sul do Brasil; Anatidae; Contaminação; Lagoa Mangueira; Metais pesados; Southern Brazil; Anatidae; Contamination; heavy metals; CIENCIAS AGRARIAS::MEDICINA VETERINARIA